A network meta-analysis: evaluating the efficacy and safety of concurrent proton pump inhibitors and clopidogrel therapy in post-PCI patients - Ai, Ming-Ying; Chen, Yan-Zuo; Kuo, Chien-Liang; Chang, Wei-Lun (Frontiers in Cardiovascular Medicine, 2024)
Introduction The objective of this research was to evaluate the risk of major adverse cardiovascular events (MACEs) associated with the use of various proton pump inhibitors (PPIs) in combination with clopidogrel in patients who underwent percutaneous coronary intervention (PCI). Methods To accomplish this, we analyzed data from randomized controlled trials and retrospective cohort studies sourced from key electronic databases. These studies specifically examined the effects of different PPIs, such as lansoprazole, esomeprazole, omeprazole, rabeprazole, and pantoprazole, when used in conjunction with clopidogrel on MACEs. The primary focus was on the differential impact of these PPIs, while the secondary focus was on the comparison of gastrointestinal (GI) bleeding events in groups receiving different PPIs with clopidogrel vs. a placebo group. This study's protocol was officially registered with INPLASY (INPLASY2024-2-0009). Results We conducted a network meta-analysis involving 16 studies with a total of 145,999 patients. Our findings indicated that rabeprazole when combined with clopidogrel, had the lowest increase in MACE risk (effect size, 1.05, 95% CI: 0.66–1.66), while lansoprazole was associated with the highest risk increase (effect size, 1.48, 95% CI: 1.22–1.80). Esomeprazole (effect size, 1.28, 95% CI: 1.09–1.51), omeprazole (effect size, 1.23, 95% CI: 1.07–1.43), and pantoprazole (effect size, 1.38, 95% CI: 1.18–1.60) also significantly increased MACE risk. For the secondary outcome, esomeprazole (effect size, 0.30, 95% CI: 0.09–0.94), omeprazole (effect size, 0.34, 95% CI: 0.14–0.81), and pantoprazole (effect size, 0.33, 95% CI: 0.13–0.84) demonstrated an increased potential for GI bleeding prevention. Conclusions In conclusion, the combination of lansoprazole and clopidogrel was found to significantly elevate the risk of MACEs without offering GI protection in post-PCI patients. This study is the first network meta-analysis to identify the most effective regimen for the concurrent use of clopidogrel with individual PPIs. Systematic Review Registration https://inplasy.com/inplasy-2024-2-0009/, identifier (INPLASY2024-2-0009).